ANALISIS PERBEDAAN KUALITAS CITRA DAN INFORMASI ANATOMI PADA PEMERIKSAAN MRI LUMBAL SEKUEN T2WI FAST SPIN ECHO (FSE) POTONGAN SAGITAL DENGAN VARIASI NILAI TIME REPETITION - Merah Bagus YB; Darmini Darmini; Sri Mulyati (JRI (Jurnal Radiografer Indonesia), 2020)
Background: Lumbar MRI examination at T2 weighted is recommended using the Fast Spin Echo (FSE) sequence because it can detect early symptoms of a pathology, such as edema, tumors, infections, fractures, ligament injuries, and produce images with strong signals in CSF including details of nerve roots. Based on the observations of researchers at MRCCC Siloam Hospital Semanggi Jakarta that uses TR values ​​in the range of 3500-7500 ms with 3 Tesla MRI. This study aims to determine the differences in image quality and anatomical information as well as knowing the TR values ​​that produce best quality and anatomical information on Lumbar MRI on T2WI FSE. Methods: This type of research is an experiment, then a different friedman test was carried out to determine differences in image quality and anatomical information with variations in TR values ​​that produced best image quality and anatomical information. Result: Friedman test shows there are significant differences between the variation of TR on anatomical information produced with p-value < 0.001. The friedman test results obtained p-value SNR < 0.001, CNR < 0.001 and scan time < 0.001. TR which produces best image quality and anatomical information is TR 5500ms with mean rank 2.32 on Lumbar MRI examination by T2WI FSE sequence sagital slices.